1999
DOI: 10.1007/s001270050146
|View full text |Cite
|
Sign up to set email alerts
|

Patient and relative education in community psychiatry: a randomized controlled trial regarding its effectiveness

Abstract: A short patient and relative education programme seems to be able to influence knowledge and some aspects of satisfaction, but does not seem to be sufficient to influence important variables such as relapse, compliance, psychopathology, insight or psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 39 publications
6
88
1
5
Order By: Relevance
“…Most studies of psychoeducation for patients only have demonstrated that knowledge and adherence can be improved by means of educational interventions 9 . Studies using more didactic formats have influenced improvements in general understanding of schizophrenia and treatment [10][11][12] . Evidence exists that even comparatively brief interventions can achieve significant improvements in patients with chronic psychiatric disorders 10,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of psychoeducation for patients only have demonstrated that knowledge and adherence can be improved by means of educational interventions 9 . Studies using more didactic formats have influenced improvements in general understanding of schizophrenia and treatment [10][11][12] . Evidence exists that even comparatively brief interventions can achieve significant improvements in patients with chronic psychiatric disorders 10,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using more didactic formats have influenced improvements in general understanding of schizophrenia and treatment [10][11][12] . Evidence exists that even comparatively brief interventions can achieve significant improvements in patients with chronic psychiatric disorders 10,[12][13][14] . A recently published meta-analysis conducted by Lincoln, Wilhelm & Nestoriuc 15 suggests, however, that psychoeducation for patients only can not be considered effective.…”
Section: Introductionmentioning
confidence: 99%
“…66 Results revealed a statistically significant increase in knowledge of schizophrenia and aspects of satisfaction in both relative and patient programs at postintervention. Further, the educational interventions were found to be useful in improving communication skills regarding treatment and more existential issues.…”
Section: Other Nonpharmacological Therapeutic Strategiesmentioning
confidence: 93%
“…The relevance of cultural factors to both diagnosis and treatment suggests potential benefits of identifying personal and cultural factors and integrating that understanding into the provision of care, including psychoeducation and other interventions to address culturally related stigma and shame. Such an approach has been recommended by experts (Mezzich et al 2009;Yamada and Brekke 2008) and organizations, including the APA (DSM-5 Cultural Formulation Interview; American Psychiatric Association 2013a), The Joint Commission (2010,2011), and the Office of Minority Health of the U.S. Department of Health and Human Services (2014).…”
Section: Rationalementioning
confidence: 99%